A Systematic Review of Interventions to Reduce Maternal Mortality among HIV-Infected Pregnant and Postpartum Women - Sarah A. Holtz, DrPH, MPH; Rudi Thetard, MD, MPH; Sarah N. Konopka, MA; Jennifer Albertini, MPH; Anouk Amzel, MD, MPH, FAAP; Karen P. Fogg, MPH (Global Health and Education Projects, Inc., 2015)
Background: In high-prevalence populations, HIV-related maternal mortality is high with increased mortality found among HIV-infected pregnant and postpartum women compared to their uninfected peers. The scale-up of HIV-related treatment options and broader reach of programming for HIV-infected pregnant and postpartum women is likely to have decreased maternal mortality. This systematic review synthesized evidence on interventions that have directly reduced mortality among this population. Methods: Studies published between January 1, 2003 and November 30, 2014 were searched using PubMed. Of the 1,373 records screened, 19 were included in the analysis. Results: Interventions identified through the review include antiretroviral therapy (ART), micronutrients (multivitamins, vitamin A, and selenium), and antibiotics. ART during pregnancy was shown to reduce mortality. Timing of ART initiation, duration of treatment, HIV disease status, and ART discontinuation after pregnancy influence mortality reduction. Incident pregnancy in women already on ART for their health appears not to have adverse consequences for the mother. Multivitamin use was shown to reduce disease progression while other micronutrients and antibiotics had no beneficial effect on maternal mortality. Conclusions: ART was the only intervention identified that decreased death in HIV-infected pregnant and postpartum women. The findings support global trends in encouraging initiation of lifelong ART for all HIV-infected pregnant and breastfeeding women (Option B+), regardless of their CD4+ count, as an important step in ensuring appropriate care and treatment. Global Health Implications: Maternal mortality is a rare event that highlights challenges in measuring the impact of interventions on mortality. Developing effective patient-centered interventions to reduce maternal morbidity and mortality, as well as corresponding evaluation measures of their impact, requires further attention by policy makers, program managers, and researchers.